Transparent neural implantable devices: a comprehensive review of challenges and progress - Young Uk Cho; Se Lin Lim; Jung-Hoon Hong; Ki Jun Yu (npj Flexible Electronics, 2022)
Abstract The key to designing an implantable device lies in condensing the synergistic effects of diagnostic and therapeutic methods in a single tool. In conjunction with the integration of electrophysiology and optical modalities, a transparent neural interface alleviates challenges of conventional metal-based microelectrodes. In this review, the multimodal sensing and stimulation functionalities of recent research are addressed. Next, issues that arise when combining functionalities of conventional metal-based, opaque electrode arrays together with optical modalities—(1) photoelectric artifacts, (2) optical image blocking, and (3) light transmission efficiency—are introduced. Then, an introduction of advancing material candidates for transparent neural interfaces follows with the latest research.